2017
DOI: 10.1111/joic.12459
|View full text |Cite
|
Sign up to set email alerts
|

Vascular complications after percutaneous mitral valve repair and venous access closure using suture or closure device

Abstract: Both Z-suture and closure device use after percutaneous mitral valve repair are feasible and safe. However, there is no benefit of one strategy over the other according to VARC2 major and minor complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Moreover, due to the elastic venous wall properties, the access site sealing and healing is fast and standard manual compression is an effective and safe method in achieving hemostasis. However, several studies have shown that temporary figure-of-eight suture (Z-suture) is a useful tool in achieving hemostasis by compression of the femoral vein through wrapped and folded subcutaneous soft tissue (14). On the other hand, preclosure suture with the Proglide® (Abbott Vascular Inc., Santa Clara, California) device for larger-sized venous sheaths proved to be safe and allowing an early mobilization (15).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to the elastic venous wall properties, the access site sealing and healing is fast and standard manual compression is an effective and safe method in achieving hemostasis. However, several studies have shown that temporary figure-of-eight suture (Z-suture) is a useful tool in achieving hemostasis by compression of the femoral vein through wrapped and folded subcutaneous soft tissue (14). On the other hand, preclosure suture with the Proglide® (Abbott Vascular Inc., Santa Clara, California) device for larger-sized venous sheaths proved to be safe and allowing an early mobilization (15).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have proved the safety and feasibility of the PVCD during interventional procedures [ 3 - 6 ]. In particular, ProGlide was found to perform better than other PVCDs in interventional research [ 9 - 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The traditional approach of femoral cannulation is to make a small incision in the inguinal area and to access the femoral vessels ( Fig. 3A, B ) [ 2 , 6 ]. The open surgical technique for femoral cannulation may have some disadvantages compared to percutaneous cannulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations